Masalah-masalah Etis Pendidikan Humaniora Melalui Media Digital - Alexander Aur (Center for Philosophy and Ethics, 2020)
Humanities education - as a way for educators and students to develop dimensions of the human self to be more human - is facing a serious ethical challenge. The challenge in question is regarding the ontological status of digital media. The philosopher Martin Heidegger said that technology is the mode and moment of alētheia, that is, being reveals itself. Being reveals himself, that is the truth. When humans use technological tools, that is the moment and the way humans understand and embrace the truth. That's the technological ontology. Referring to the technological ontology, there are ethical problems faced by educators and students in the context of humanities learning through digital media. First, educators and students strive for an ontology of digital technology so that together with the use of digital technology, ethical truth and goodness reveal themselves. Second, educators and students open themselves to the truth and ethical virtues that reveal themselves during online humanities learning. Thus, educators and students remain ethical and human beings in the digital age.